E-Readiness Assesment dalam Menilai Tingkat Kesiapan Penggunaan Teknologi Informasi di Lingkungan Kementerian Agama Provinsi Jawa Barat - Afiyah, Salamatul; Alia, Siti; Wahyu, Fitri Pebriani (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2022)
The purpose of this research is to determine the level of readiness or readiness of human resources and the community as users / Users of the West Java Provincial Religious Affairs Office services towards the use of IT and what is needed to improve and develop the existing level of readiness. These efforts can pave the way to integrate services that were previously separate into a one-stop service that is easily accessible to the public with just one account. This research uses the Mixed Method Research (MMR) MMR is a research method that brings together two research approaches in one study, namely qualitative research and quantitative research. E-readiness or readiness of officers in operating this online-based KUA service is mostly quite ready. Judging from the facilities and infrastructure such as computers, printers, and IT devices, however, there needs to be more attention to KUAs in rural environments that are often constrained by networks. In addition, there is a need for feature improvements to be made in a short period of time. Most of the KUAs already have adequate facilities and infrastructure. Meanwhile, in terms of the community, people tend to prefer to visit the office directly rather than having to register online. This is because there are still many people who do not know about the existence of online-based applications at the KUA and people who are not too technologically literate. So there needs to be an increase in socialization efforts made to the community.